Epistemology and education: learning sciences and educational research from an epistemological perspective - Gisella Boarini, María (2020)
In the present paper an analysis of the epistemological foundations on which the educational field has been founded since its origin until today is made, in order to understand in depth the current situation of educational research. To this end, a historical-epistemological study is carried out. This study seeks to uncover the justification that, in each moment and context, has founded the said field. This path shows that, at first, historicity (referred to the contextual, non-rational, non-scientific) was deliberately set aside to guarantee the development of a rational science. Later, and due to the persistence of certain epistemological problems, this historicity is understood as a value and becomes the disciplinary foundation. The work argues that the use of historicity as a criterion of justification (either to eliminate it or to use it) is not sufficient criterion to base the field. It requires a criterion that transcends the limits of the discipline itself and allows to face the problems related to historicity and consequent incommensurability.